Jane Tolmach for Assembly 36th District - Jane Tolmach::::::
This document is a campaign letter from Jane Tolmach for Assembly in California's 36th District. In the letter, Tolmach reaffirms her commitment to representing residents, taxpayers, and individuals first if elected to the State Assembly. She emphasizes her longstanding belief in serving people as individuals who deserve integrity and responsiveness from elected officials. She highlights the broad support she has received from respected community leaders in the district as evidence of her fairness, compassion, and sensitivity to constituents' needs. Tolmach points to her prior experience as a City Council Member and School Board Trustee, stating that she has demonstrated independent judgment and fairness in public service. She contrasts her "proven record of public service, experience and performance" with "just a lot of promises" and pledges to be a hard-working, effective, and honest Assembly representative. The letter closes with a request for voters' support and their vote on November 2nd, and includes campaign headquarters information in Oxnard and Ventura, along with a list of community supporters.